Track-II Diplomacy in the Format of Situational Analysis: The Experience of the Institute of Oriental Studies of the Russian Academy of Sciences - A. K. Alikberov; V. V. Naumkin (Vestnik MGIMO-Universiteta)
This paper examines the practice of implementing Track-II diplomacy as practiced by the Institute of Oriental Studies of the Russian Academy of Sciences (IORAS) in the form of situational analysis, a methodology developed by Academician Yevgeny Primakov. This approach represents an effective tool for resolving international conflicts and enhancing global security by combining science with diplomacy. Special attention is given to a series of three expert discussions on the Concept of Collective Security in the Persian Gulf region, held at IORAS from 2019 to 2023. These discussions demonstrated the method's ability to bring together a broad range of experts for in-depth interdisciplinary analysis of complex international situations. The practical focus of the results from these situational analyses makes them valuable for both policy recommendations and long-term strategic planning. The application of this method fosters the creation of trustful relationships between conflicting parties and the establishment of sustainable mechanisms for international security. The paper also highlights the significance of this practice for the development of Russian foreign policy strategy and its contribution to the interdisciplinary study of international relations.